“A gente tá falando de deixar viver uma galera que morre”: práticas profissionais de terapeutas ocupacionais junto à população dissidente de gêneros e sexualidades no cenário brasileiro - Leite, Jaime Daniel Junior (Universidade Federal de São Carlos, 2024)
Lesbians, gays, bisexuals, travesties, transsexuals, queers, intersexuals, asexuals, pansexuals, non-binary, among other people who experience dissidence of genders and sexualities, have their lives marked through violence. This fact can lead to the intensification of fragilities, reconfiguring the organization of these people's everyday lives, with wide-ranging impacts ranging from the sphere of personal, affective and loving relationships (in friendship, family, marital life, religious options) to that social policies (health, education, social assistance, among others). In occupational therapy, work in the field of gender and sexual dissidence is scarce, with almost no bibliographical production on the subject. Taking Judith Butler's reflections on the construction of alliances between groups that aim for social justice – as justice in conceptualized by Nancy Fraser – a theoretical-methodological alliance between social occupational therapy, critical occupational science and queer studies was proposed. Through a survey done to apprehend and analyze the professional profile and practices of occupational therapists who work in Brazil with this public, elements were gathered to support the hypothesis that the work occupational therapists carried out with the population who experience dissidence of genders and sexualities did not bring new resources or technology specific to the professional core. No practices were identified exclusively for the care of this population. It was noted that the professionals used resources already known and established in the field. The main differentiating factor between practices that operated within the logic of adaptation or social articulation were the theoretical-methodological references used. The first stage of the research was a scoping review of journal articles indexed in academic databases and virtual libraries, namely: VHL, CINAHL, SciELO Citation Index, SCOPUS and Web of Science. Considering articles available online until March 2021,39 articles were included in the review. In the second stage, an online questionnaire (2019-2020) to understand practice with this population. Using snowball sampling, recruitment began through seed informants and social media. Based on the responses (n= 95), 15 informants were selected for interviews to enhance depth of understanding of the professional practice developed. Using Laurence Bardin's postulates, we used thematic content analysis to organize and process field data. Even though we can affirm that there are occupational therapists in Brazil working with the population who experience dissident genders or sexualities, when we consider the literature, few productions focused specifically on professional practice. Most articles proposed possible contributions and made general recommendations. Taking these findings, we seek to offer support so that occupational therapy continues to work with the population in question, but also point to the necessity of critical reflection on this field of knowledge and practices. In these assumptions, a complex, diverse profession is defended, with its multiple possibilities of intervention, different vocabularies and objects, but which builds common general objectives focused on people’s participation that requires social justice. Thus, occupational therapy remains a field of borders, but building alliances with references will converge in a reading of the world and the collective task.
“We are talking about letting people who are dying live”: professional practices of occupational therapists with people who experience dissidence of genders and sexualities in the brazilian context
Keywords: Terapia ocupacional social; Aliança; Minorias sexuais e de gênero; Prática profissional; Justiça social; Social occupational therapy; Alliance; Sexual and gender minorities; Professional practice; Social justice; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL